'The Slaves of Chance': Aspects of the Exposition of Change in Some of Shakepeare's Works and their Sources - Peters, John Lionel (Department of English Language and Literature, 2017)
Rather than the assertion of a pre-defined thesis, this study is an empirical investigation of the bearing that the exposition of change in some of Shakespeare's sources may have upon his work. The first chapter, devoted to the poems Venus and Adonis and The Rape of Lucrece, points to the significance of the Time-Fortuna-Occasio topoi and of· genre conventions in Early Modern discourse on change; and seeks to identify some of the complexity in Shakespeare's use of them. An appendix to the chapter addresses the question of the inconsistency of discourse in the source-texts. In the remaining chapters a discussion of issues relating to the exposition of change in the source-texts precedes some consideration of the relevance of these issues to the plays themselves. Chapter Two is primarily, concerned with Edward Hall's Chronicle and the Henry VI plays, but also contains a broader discussion of Renaissance historiography that includes Samuel Daniel's The Civil ~ and the influence of Machiavelli. In Chapter Three a discussion of the preoccupation of Euphuistic fictions with the forces that bear upon youth (the opposing attractions of the Active and Contemplative lives, the assaults of Fortune) centres on Greene's Pandosto and Lodge's Rosalynde (the sources of The Winter's Tale and As You Like It) . In Chapter Four discussions of the Boethian element in Chaucer's Troilus and Criseyde, the rhetoric of change in Lydgate's Troy Book, and the debt owed to both works by Brooke's pseudo-medieval Romeus and Juliet point to elements of subversion in Troilus and Cressida and Romeo and Juliet. In Chapter five readings of Hamlet and Macbeth are suggested by a reconsideration of their sources in relation to sixteenth century political and religious controversy. The Conclusion suggests a context in literary criticism within which the findings of the investigation may be placed.